Spanish Validation of the Conflict Tactics Scale-Parent to Child: Assessing Non-Violent Discipline, Coercive Discipline, and Physical Aggression - Dominguez, Danilo; Pérez-Testor, Carles; Benedico-Peydró, Paula; Casarramona, Aina; Aznar-Martínez, Berta (Frontiers in Psychology, 2025)
IntroductionThere is a gap in the available Spanish-language instruments that specifically measure the behaviors or tactics used by parents in conflict or hostile situations with their children. The main objective of this study was to translate, adapt, and validate the Conflict Tactics Scale: Parent to Child (CTSPC) within the Spanish context, evaluating its psychometric properties, including exploratory factor analysis, confirmatory factor analysis, and internal consistency.MethodA sample of 700 parents (350 women and 350 men) aged between 18 and 69 years was used.ResultsThe Spanish version of the CTSPC consists of 21 items distributed across 3 dimensions: Non-Violent Discipline (α = 0.71), Coercive Discipline (α = 0.81), and Physical Aggression (α = 0.93). The findings indicated that 14.14% of participants reported having used physically aggressive behaviors toward their children at least once in their lifetime.DiscussionThis instrument emerges as a valuable tool for identifying inappropriate tactics and behaviors employed by parents toward their children, contributing to the prevention of child maltreatment and raising parental awareness about how to educate children without resorting to violence.